Determinants of Employee Engagement in Nepalese Commercial Banks - Kharel, Shreekrishna; Niraula, Ganesh Prasad; Mainali, Bhawani Prasad (Journal of Balkumari College, 2024)
This article aims to determine the major factors that determine employee engagement and how predictable the idea is for users. The impact of relationships is examined through a cross-sectional survey. The study had a finite population of 46508 employees, of which 384 were selected at random from ten commercial banks in Nepal to serve as respondents. The data were collected using a standardized Likert Scale questionnaire, where 1 indicated strongly disagree and 5 indicated strongly agree. Regression was used to analyze the data. A metric for assessing reliability has been the Chronbach’s Alpha value which was (0.823) on an average for all the variables. A questionnaire for the survey was employed. The employees from managerial and operational levels of Nepalese commercial banks were chosen using simple random sampling. 384 genuine answers to the 430 questionnaires that were distributed were collected. The associations were estimated and predicted using regression analysis. It was found that all of the variables that were proven to be significant predictors of employee engagement (r2 = 0.41) included the training and advancement, career development, performance management and job security. The primary objective of this study is the requirement for proactive, comprehensive ways to identifying factors initiatives in order to assure alignment with business objectives and prioritize employee engagement.